Electronic transport and thermoelectric properties of phosphorene nanodisk under an electric field - Bazrafshan, M. Amir; Khoeini, Farhad (Frontiers in Physics, 2023)
The Seebeck coefficient is an important quantity in determining the thermoelectric efficiency of a material. Phosphorene is a two-dimensional material with a puckered structure, which makes its properties anisotropic. In this work, a phosphorene nanodisk (PDisk) with a radius of 3.1 nm connected to two zigzag phosphorene nanoribbons is studied, numerically, by the tight-binding and non-equilibrium Green’s function (NEGF) methods in the presence of transverse and perpendicular electric fields. Our results show that the change in structure from a zigzag ribbon to a disk form creates an energy gap in the structure, such that for a typical nanodisk with a radius of 3.1 nm, the size of the energy gap is 3.88 eV. Besides, with this change, the maximum Seebeck coefficient increases from 1.54 to 2.03 mV/K. Furthermore, we can control the electron transmission and Seebeck coefficients with the help of the electric fields. The numerical results show that with the increase of the electric field, the transmission coefficient decreases and the Seebeck coefficient changes. The effect of a perpendicular electric field on the Seebeck coefficient is weaker than a transverse electric field. For an applied transverse electric field of 0.3 V/nm, the maximum Seebeck coefficient enhances to 2.09 mV/K.